2000
DOI: 10.1002/(sici)1096-8628(20000424)91:5<368::aid-ajmg10>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

WHIM syndrome, an autosomal dominant disorder: Clinical, hematological, and molecular studies

Abstract: The acronym WHIM refers to Warts, Hypogammaglobulinemia, Infections, and Myelokathexis. The latter refers to the retention of white cells in the marrow, which becomes hypercellular. We have found approximately 20 examples of WHIM syndrome in the literature under various designations; the first examples are Zuelzer [1964] and Krill et al. [1964]. Chronic noncyclic neutropenia and hypercellular bone marrow represent defective release of marrow cells into the peripheral stream (myelokathexis). The hypermature neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
79
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(80 citation statements)
references
References 38 publications
(32 reference statements)
0
79
0
1
Order By: Relevance
“…44 G-CSF regulation of CXCR4 has gained much attention as a critical pathway for HSPC release in response to G-CSF. While the role of CXCR4 in the mobilization of myeloid cells, particularly with a contribution of CXCR2, is well-documented, 7,8,10,[13][14][15][16]45 its role in the mobilization of HSPC is not well documented. Previous studies showed that G-CSF administration in man induces a gradual increase in the expression of CXCR4 on bone marrow progenitors (CD34 + or CD38 + cells) over 5 days of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44 G-CSF regulation of CXCR4 has gained much attention as a critical pathway for HSPC release in response to G-CSF. While the role of CXCR4 in the mobilization of myeloid cells, particularly with a contribution of CXCR2, is well-documented, 7,8,10,[13][14][15][16]45 its role in the mobilization of HSPC is not well documented. Previous studies showed that G-CSF administration in man induces a gradual increase in the expression of CXCR4 on bone marrow progenitors (CD34 + or CD38 + cells) over 5 days of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] Patients with WHIM (warts, hypogammaglobulinemia, infections, myelokathexis) are neutropenic because of reduced neutrophil mobilization attributable, in most cases, to "gain-of-function" mutations of CXCR4. 13,14 Selective deletion of CXCR4 in myeloid cells causes a redistribution of neutrophils from the bone marrow to the blood resulting in neutrophilia. 10 AMD3100, a synthetic inhibitor of SDF1 binding to CXCR4, promotes neutrophil mobilization when injected into mice and humans.…”
Section: Introductionmentioning
confidence: 99%
“…Complete deletion of Gfi1 results in runting and inner ear defects in the mouse model 8 , but humans with amino acid substitutions show no evidence of these or other developmental problems. The combined neutropenia and immunodeficiency resembles the WHIM syndrome of myelokathexis 9 , but the undifferentiated appearance of the neutrophils differs from the hypermature appearance of neutrophils in WHIM syndrome.…”
mentioning
confidence: 99%
“…Several studies have evaluated IL-2 treatment of CD4 + lymphopenia because of HIV. Generally, these IL-2 treatments in HIV lymphopenia studies have revealed significant increases in CD4 + counts and possible clinical improvement in immunological function [16][17][18][19]. From these large studies the sideeffect profile of IL-2 in HIV CD4…”
Section: Discussionmentioning
confidence: 99%
“…The patient's lack of warts on physical examination, Ig profile, bone marrow biopsy findings and normal neutrophil counts were inconsistent with the warts, hypogammaglobulinaemia, infection and myelokathexis syndrome [16]. A very small number of case reports have described variant partial adenosine deaminase (ADA) deficiency that presents first in adults [17,18].…”
Section: Methodsmentioning
confidence: 99%